Search for boosted diphoton resonances in the 10 to 70 GeV mass range using 138 fb −1 of 13 TeV pp collisions with the ATLAS detector. (Tufts University. Tisch Library., 2023)
Keywords : Hadron-Hadron Scattering, Beyond Standard Model.; Springer Open.